Pola Komunikasi Badan Kesatuan Bangsa dan Politik dalam Pencegahan Tindakan Terorisme di Kabupaten Poso - Rizkia, Anita Indah (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to determine how communication patterns and inhibiting factors of the Poso Regency National and Political Unity Agency in preventing acts of terrorism, descriptive qualitative research method. Subject Employees of the Poso Regency National and Political Unity Agency, with the object of the Poso Regency National and Political Unity Agency. Conducting interviews with employees of the Poso Regency National and Political Unity Agency. The results of this study indicate that in the prevention carried out by the National and Political Unity Agency there is a linear communication pattern, and in its prevention there are several inhibiting factors. 1). The existing linear communication pattern is socialization and counseling carried out by the National Unity and Political Unity Agency in preventing acts of terrorism, In this communication process, the message conveyed by the National Unity and Political Unity Agency will be effective if there is planning before carrying out communication. 2). The National Unity and Political Agency of Poso Regency in carrying out prevention gets several obstacles, namely language barriers, there are still sympathizers who make it difficult for the National Unity and Political Agency to carry out prevention, besides that in conducting counseling the National Unity and Political Agency of Poso Regency gets a language barrier in communicating during socialization.